تأثير الفطر Ascochyta fabae f. Sp. Lentis المسبب لمرض لفحة أسكوكيتا العدس في بعض أصناف العدس المزروعة في المنطقة الغربية من سوريا - المغربي, صباح; اسعد, سهام; عيسى, ميلاد (Latakia University Journal -Biological Sciences Series, 2013)
تعتبر لفحة الأسكوكيتا، التي يحدثها الفطر Ascochyta fabae f. Sp. Lentisمن الأمراض الفطرية المهمة التي تصيب العدس وتسبب أضرارا" كبيرة له . نفذت التجربة الحقلية في محطة بحوث إيكاردا للتجارب الزراعية في منطقة بستان الباشا، جبلة، اللاذقية. على أربعة أصناف من العدس التي تزرع في مناطق مختلفة من سورية وهذه الأصناف هي: ادلب2، ادلب3، ادلب4، والبلدي الأحمر. تم إجراء العدوى الاصطناعية باستخدام عزلة محلية من الفطر Ascochyta lentis بمعدل ثلاث مرات بفارق عشرة أيام بين كل عدوى وأخرى، واعتمد اللقاح المعدي بتركيز510 بوغة/ملل . أظهرت النتائج أن نسبة وشدة الإصابة بهذا الفطر عند بعض الأصناف وبخاصّةٍ صنف ادلب4 كانت عالية (%33.82)، وإنّ الصنف البلدي الأحمر هو الأكثر مقاومةً لفطر الأسكوكيتا (%10.09) مقارنةً مع باقي الأصناف المزروعة تحت ظروف التجربة. كما بيّنت الدراسة أنّ وزن الألف حبة للأصناف الحساسة كان أقل مقارنةً بالشاهد الغير معدى،حيث أدى الإعداء الإصطناعي إلى فقد في وزن الألف حبة الذي بلغ متوسطه (33.51 غ) مقارنةً مع الشاهد (36.86 غ) كمتوسط عام للأصناف الأربعة وتبين أن الصنف ادلب4 هو أكثر الأصناف تأثرا بانخفاض وزن الألف حبة قياسا" بباقي الأصناف . Ascochyta blight, which is caused by the fungus Ascochyta fabae f. Sp. Lentis, is considered as a very important fungal disease that infects lentils and cause it damage. The experiment was conducted in ICARDA research station for agricultural experiments in the orchard area Basha, Jableh, Lattakia in four varieties of lentils that are grown in different parts of Syria, and these varieties are: Idleb 2, Idleb 3, Idleb 4, and municipal red. Artificial infection was performed using a local isolation of the fungus Ascochyta lentis with an average of three times and ten days between each infection and the other. The infectious vaccine adopted a concentration of 105 Båge / ml. The results showed that the rate and severity of this injury for some mushroom varieties ,especially Idlib Class 4, was high (33.82%). The Municipal Class Red was the most resistant to the blight fungus (% 10.09) compared with the rest of the cultivated varieties under the conditions of the experiment. The study also demonstrated that the weight of a thousand tablets of sensitive varieties was lower compared to the non-contagious control, where the artificial infection led to the loss in weight of a thousand tablets which averaged (33.51 g) compared with the control (36.86 g) as a total average for the four classes and show that Idleb 4 is the most affected with the weight loss of thousand-grain compared to the rest of the varieties.